An overview of buckling, burst and corrosion analyses on pre-stressed thermosetting glass fiber-reinforced polymer tubular structures - Mdd. Nordin, Nur Naqiuddin (2020)
Glass Fiber-Reinforced Polymer (GFRP) tubular structures can withstand the hydrostatic forces by positioning the fibers in the tangential direction to increase the hoop strength, making the GFRP tubular structures anisotropically stronger than its metal counterparts. However, there are more underlying factors to be considered for GFRP to be the alternative to metallic structures. The paper aims to study the buckling, burst and corrosion analyses for pre-stressed GFRP tubular structures for aboveground, underground and subsea environments in both horizontal and vertical applications. The effects of increased stiffness from the pre-stressed structures on crack angle and length are studied in depth along with the effect of wall thickness and curing effect on the structural integrity. Moreover, the seawater and chemical corrosion effects on the impact resistance of thermosetting structures are investigated.